2020
DOI: 10.1515/snde-2018-0087
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics between the budget deficit and the government debt in the United States: a nonlinear analysis

Abstract: AbstractThis paper empirically investigates the dynamics between budget deficit and government debt in the U.S. using two different measures of the budget deficit: the current budget deficit and cyclically-adjusted budget deficit. A threshold Vector autoregression (VAR) model is estimated to explore the dynamics in different regimes using quarterly data from 1947:Q1 to 2017:Q3. The specification test rejects a linear VAR model against the threshold VAR. When we use the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…For an economy to satisfy its intertemporal budget constraint and the so-called no-Ponzi condition, the coefficient θ > 0 is sufficient provided the present value of GDP is finite and ξ t < ∞ as a fraction of GDP as well. 2 However, other studies 3 have shown that a positive coefficient θ cannot be viewed as a sufficient condition to achieve fiscal sustainability, especially if there is a limit for positive values of primary balance, for instance, at a very high debt level, or if the reaction of financial market is…”
Section: Model and Datamentioning
confidence: 99%
See 2 more Smart Citations
“…For an economy to satisfy its intertemporal budget constraint and the so-called no-Ponzi condition, the coefficient θ > 0 is sufficient provided the present value of GDP is finite and ξ t < ∞ as a fraction of GDP as well. 2 However, other studies 3 have shown that a positive coefficient θ cannot be viewed as a sufficient condition to achieve fiscal sustainability, especially if there is a limit for positive values of primary balance, for instance, at a very high debt level, or if the reaction of financial market is…”
Section: Model and Datamentioning
confidence: 99%
“…The explanatory power as measured by the goodness of fit statistics is 0.525. In column [2], including the time fixed effect in the Base model improves the explanatory power. The FRF coefficient is slightly lower and remains statistically significant.…”
Section: Baseline Estimate and Extended Modelsmentioning
confidence: 99%
See 1 more Smart Citation